PERILAKU KOMUNIKASI PENGGUNA MEDIA SOSIAL LINE PADA MAHASISWA JURUSAN ILMU KOMUNIKASI ANGKATAN 2012 - ernianti ernianti (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT The problem of this research is how the communication behavior of users of social media line in communication science students majoring in force in 2012.the location of research in the university district halu oleo communication sciences faculty of social sciences and political science, with informants forces communications science majors in 2012 as many as 7 people, determination of the informants in this study, conducted by purposive sampling (refer directly). Collecting data using observation and interview (interviews), data sorces, namely primary and secondary data were then analyzed using qualitative descriptive technique. The results of this study indicate that the communication behavior of social media line at students majoring in communication science class 2012 refers to the desire within every student to consider what people in the media like to use social media line, they use the line for students to be more interested in using social media line compared to other social media. Students majoring in science communication using social media because the line because the line has many features provided in it including sticker, free phone calls and video calls. While other social media such as facebook, blackberry messenger, and whatsapp can not compete with the charm sticker offered by line. Because the sticker on social media line can represent our feelings at the time chatting ang having and animated picture that can move on its own. Keyword : communication behavior, line social media, communication science students.